Pengembangan Model Bahan Ajar Pendidikan Lingkungan Berbasis Masalah untuk Siswa Sekolah Dasar - Bhakti Karyadi (IJEEM - Indonesian Journal of Environmental Education and Management, 2016)
This research aims to develop teaching materials model of Environmental Education Base on Problem (EEBP) for sixth grade students elementary school. Development of teaching materials EEBP method refers to the model of instructional design. Teaching materials developed is evaluated by education practitioners, and then effectiveness test the group of six graders, with using the experimental method. Evaluation data analyzed by descriptive, while the effectiveness of the test data were statistically analyzed using t-test. Evaluation results can be concluded, the purpose and scope of the material in the teaching materials model EEBP have compatibility with the competencies to be achieved. Design of teaching materials draw a learning activities with problem solving approach. Statistical analysis showed that, the group of students who are taught using teaching materials EEBP have a better understanding than the group of students who are learning without the use of teaching materials EEBP. Conclusion of the study, teaching materials EEBP effective enough to improve the understanding of sixth grade students about concepts of ecosystems.